MOLECULAR MAN IN A MOLECULAR WORLD:*): Applied physicology - Nyborg, Helmuth (Psyke & Logos, 2022)
*) Invited chapter for Psyche & Logos in connection with the Danish »Year of the Brain Initiative«, 1997. All psychological explanations of (human) nature involve by definition references to psychic or mental qualities, presumed to exist above the material world. They come principally in three different versions, none of which are in accord with a proper scientific approach, however. The chapter therefore first illustrates some of the insurmountable problems that face the psychological approach, and then suggests an alternative solution in form of a physicological research program. (Human) nature (and society) is, according to this program, better described in terms of the underlying molecular processes that carry them. Examples of application of the physicological analysis are demonstrated, one via a molecular model for genius, another by a critical discussion of various forms of consciousness and moral. The chapter finally touches on relevant aspects of thermodynamics, on how traditional physics relates to physicology, and on why the mentalist critique of physicology as reductionism totally misses the point.